Experimental and numerical (EFG method) studies on sedimentary rock under varied salinity conditions. (December 2021) - Dinesh, P.; Ranjith, P.G.; Behera, M.R.; Muthu, N.
Abstract: In this paper, uniaxial compressive strength (UCS) tests were performed on cylindrical Gosford sandstone specimens of varying salinity to quantify the degradation in the modulus of elasticity properties. Three-point bending (TPB) tests of a single-edge notched beam (SENB) were performed to estimate the fracture toughness. To accurately model the phenomenon of degradation in the presence of non-homogeneity and varying salinity, a modified element-free Galerkin (EFG) method was used. A mesoscopic representative volume element (RVE) of the Gosford sandstone sample that accounts for the rock salt formation in pore spaces was considered within the framework of the modified EFG method. The degradation observed in the experimental UCS studies was incorporated into modelling at a mesoscale. The effective mesoscale parameters were incorporated into the macroscale to obtain load-displacement behaviour, in TPB tests of the SENB samples, through the principle of homogenisation. Additionally, the EFG method has been used to predict the crack path in sedimentary rocks that are subjected to mixed-mode loading. The curved crack path thus obtained is in good agreement with the existing results in the literature.